Testing the impact of satellite anisotropy on large- and small-scale intrinsic alignments using hydrodynamical simulations. Issue 4 (14th November 2019) - Samuroff, S; Mandelbaum, R; Di Matteo, T
ABSTRACT: Galaxy intrinsic alignments (IAs) have long been recognized as a significant contaminant to weak lensing-based cosmological inference. In this paper we seek to quantify the impact of a common modelling assumption in analytic descriptions of IAs: that of spherically symmetric dark matter haloes. Understanding such effects is important as the current generation of IA models are known to be limited, particularly on small scales, and building an accurate theoretical description will be essential for fully exploiting the information in future lensing data. Our analysis is based on a catalogue of 113 560 galaxies between z = 0.06 and 1.00 from massiveblack-ii, a hydrodynamical simulation of box length 100 h^-1 Mpc. We find satellite anisotropy contributes at the level of 30\!-\!40 per cent to the small-scale alignment correlation functions. At separations larger than 1 h^-1 Mpc the impact is roughly scale independent, inducing a shift in the amplitude of the IA power spectra of 20 per cent . These conclusions are consistent across the redshift range and between the massiveblack-ii and the illustris simulations. The cosmological implications of these results are tested using a simulated likelihood analysis. Synthetic cosmic shear data are constructed with the expected characteristics (depth, area, and number density) of a future LSST-like survey. Our results suggest that modelling alignments using a halo model based upon spherical symmetry could potentially induce cosmological parameter biases at the ∼1.5σ level for S 8 and w .